GOOD CORPORATE GOVERNANCE AS A MODERATING VARIABLE OF THE INFLUENCE OF LEADERSHIP STYLE ON FINANCIAL PERFORMANCE - Smita Catur Sudyantara; Pemy Christian; Dio Agung Herubawa; Indra Wijaya; Musran Munizu (JURNAL ILMIAH EDUNOMIKA, 2025)
Abstract This research is a quantitative research with an explanatory approach, namely an approach that uses a number of previous studies as the main reference so that the hypothesis presented by the researcher in this study can be proven. The data used in this article is primary data that researchers obtained from employees of the PUPR Ministry spread throughout Indonesia. The data were collected through a questionnaire containing five statements, namely strongly agree, agree, normal/so-so, disagree, and strongly disagree. The collected data were analyzed using the smart PLS 4.0 analysis tool. The result in this article show that each hypothesis that the researcher put forward in this article can be proven comprehensively because the P-Values ​​are positive and below the significance level of 0.05, namely 0.003. In the first hypothesis, the Leadership Style variable can have a positive relationship direction and a significant influence on Company Performance because the P-Values ​​value of 0.003 is positive and below the significance level.. These results are due to a good Leadership Style that can make leaders and employees compact which can ultimately affect Company Performance. In addition, in the next hypothesis, the Good Corporate Governance variable can moderate the influence of the Leadership Style variable on Company Performance because of the same thing, namely the P-Values ​​value is positive and is below the significance level of 0.05, namely 0.000, which is more significant than the direct test of 0.003. Thus, the first and second hypotheses in this article can be accepted. Keywords : Good Corpotrate Governance, Financial Performance, Leadership Style